Metaphor as a Means of Forming the Concept of Narcissism in Modern American Psychology Books (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role and significance of metaphor in shaping the conceptualization of narcissism in the contemporary American psychology literature. Drawing the analysis from a corpus of highly popular psychology books published between 2000 and 2025, the study analyzes metaphorical expressions and frameworks utilized to describe narcissistic personality traits and disorders. The research uses a qualitative methodology based in cognitive metaphor theory and discourse analysis. The results indicate that metaphors not only structure the way the concept of narcissism is viewed but also reflect broader cultural peculiarities about individuality, identity, self-esteem, self-worth, self-respect and mental health in general. The provided discussion addresses the implications of metaphor usage for both medical understanding and ordinary public perception of narcissism. Ultimately, the study highlights the powerful impact of language and culture in affecting both the clinical discourse and popular opinion of narcissistic pathology, which suggests that metaphor can serve as a cognitive frame as well as a cultural reflection.